2019
DOI: 10.3390/cancers11020270
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Prognostic Gene Panel of Epithelial Ovarian Cancer Patients by a Machine Learning Model

Abstract: Epithelial ovarian cancer patients usually relapse after primary management. We utilized the support vector machine algorithm to develop a model for the chemo-response using the Cancer Cell Line Encyclopedia (CCLE) and validated the model in The Cancer Genome Atlas (TCGA) and the GSE9891 dataset. Finally, we evaluated the feasibility of the model using ovarian cancer patients from our institute. The 10-gene predictive model demonstrated that the high response group had a longer recurrence-free survival (RFS) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…It is difficult to correlate the features manually and predict the outcome of a patient in terms of tumor staging or DFS period. Therefore, we used different ML classifiers such as Random Forest, Support Vector Machine (SVM), Logistic Regression (LR), Multilayer Perceptrons (MLP), K-Nearest Neighbors (KNN), and Adaptive Boosting (AdaBoost) [22][23][24]28], which are popularly used in medical data analysis. Implementing different classifiers in Scikit-learn for the multi-class classification, the scheme of one-against-one was used for the SVM and the scheme OvR was used for Logistic Regression (LR) and other models, which gave the average of all metrics used in our analysis.…”
Section: Machine Learning Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to correlate the features manually and predict the outcome of a patient in terms of tumor staging or DFS period. Therefore, we used different ML classifiers such as Random Forest, Support Vector Machine (SVM), Logistic Regression (LR), Multilayer Perceptrons (MLP), K-Nearest Neighbors (KNN), and Adaptive Boosting (AdaBoost) [22][23][24]28], which are popularly used in medical data analysis. Implementing different classifiers in Scikit-learn for the multi-class classification, the scheme of one-against-one was used for the SVM and the scheme OvR was used for Logistic Regression (LR) and other models, which gave the average of all metrics used in our analysis.…”
Section: Machine Learning Analysismentioning
confidence: 99%
“…In recent years, the use of machine learning has gained much importance in the field of clinical study [14,15]. Recently, many researchers and clinicians have proposed the use of machine learning in the field of colorectal cancer [16][17][18] and other types of cancers [19][20][21][22][23][24]. For instance, in [25] authors used ML for prostate cancer screening and have determined the impact of few variables such as rate of change of prostate-specific antigen (PSA), age, BMI, and race on the model's accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Some machine learning algorithms are able to process large amounts of data with cloud computing. Moreover, many recent studies28,29 have indicated that machine learning can predict early biochemical recurrence after robot-assisted prostatectomy. Additionally, a prognostic genome for patients with epithelial ovarian cancer has been developed through a machine learning model.…”
Section: Discussionmentioning
confidence: 99%
“…It is forecasted that big data and bioinformatic technology will stay prevalent in the coming year [5,6,7,8,9]. Artificial intelligence (AI) has been used to diagnose and classify cancer for more than two decades.…”
Section: Introductionmentioning
confidence: 99%